Does connectivity reduce gender gaps in off-farm employment? Evidence from 12 low- and middle-income countries - Eva-Maria Egger; Aslhan Arslan; Emanuele Zucchini (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Gender gaps in labour force participation in developing countries persist despite income growth or structural change. We assess this persistence across economic geographies within countries, focusing on youth employment in off-farm wage jobs. We combine household survey data from 12 low- and middle-income countries in Asia, Latin America, and sub-Saharan Africa with geospatial data on population density, and estimate simultaneous probit models of different activity choices across the rural-urban gradient. The gender gap increases with connectivity from rural to peri-urban areas, and disappears in high-density urban areas. In non-rural areas, child dependency does not constrain young women, and secondary education improves their access to off-farm employment. The gender gap persists for married young women independent of connectivity improvements, indicating social norm constraints. Marital status and child dependency are associated positively with male participation, and negatively with female participation; other factors such as education are show a positive association for both sexes. These results indicate entry points for policy.
Keywords: J16; J21; O18; R23; 330; gender gap; youth; off-farm employment; Asia; Latin America; sub-Saharan Africa